The Feeling of Sincerity: Inner Speech and the Phenomenology of Assertion. (21st August 2018) - Gregory, Daniel
Abstract : There is a growing literature in philosophy dealing with the phenomenon of inner speech, that is, the activity of speaking to oneself in one's mind. This paper highlights a feature of inner speech which has not yet been noticed in this literature: that there is something distinctive that it is like to make a sincere assertion in inner speech (and, indeed, in external speech). The paper then traces out two implications of this observation. The first relates to the question of how we should characterise inner speech; the second relates to the question of how inner speech may play a role in self‐attributions of belief.